Foreign direct investment in renewable energy : trends, drivers and determinants - Hanni, Michael Stephen [et al] (2011)
Analyses foreign direct investment in renewable electricity generation and the manufacture of related equipment. Aims to shed light on the role of technology and finance as critical factors in the transition to a low-carbon economy and in international climate change negotiations and the drivers influencing TNCs to invest abroad and in specific host economies.